1996
DOI: 10.1136/emj.13.5.334
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of accident and emergency services by the homeless on the Wirral.

Abstract: Objective-To examine the use of accident and emergency (A&E) services by the homeless, with particular reference to the use of psychiatric services generated by this attendance. Methods-A retrospective study ofattendance registers at a large A&E department over an eight year period, during which there were 566 separate attendances by homeless patients out of a total of 421 237 adult attendances (1.3 per 1000). Results-There was no significant change in rates of attendances over the eight year period (P = 0.41)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Victor et al 6 found a higher rate of attendance at the emergency department by homeless people compared with the normal resident population (OR 2.6, 95% CI 2.0 to 3.3). Earnshaw et al 10 reviewed attendances at a large emergency department over 8 years prior to 1996 and identified 566 attendances by homeless people out of a total of 421 237 adult attendances, with no significant change in attendance rates over the period studied. The rate of 1.3 per 1000 adult attendances is lower than the rates reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Victor et al 6 found a higher rate of attendance at the emergency department by homeless people compared with the normal resident population (OR 2.6, 95% CI 2.0 to 3.3). Earnshaw et al 10 reviewed attendances at a large emergency department over 8 years prior to 1996 and identified 566 attendances by homeless people out of a total of 421 237 adult attendances, with no significant change in attendance rates over the period studied. The rate of 1.3 per 1000 adult attendances is lower than the rates reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of attendances by homeless patients has been calculated at 1.3 per 1000 adult attendances. 5 The aim of this study was to profile our "regular attenders" to identify how many actu-ally fit the category of "regular attenders" and estimate the percentage of the overall workload of the department attributed to this group of patients. In addition, we also aimed to examine the number of alcohol related attendances and the proportion of patients classified as having no fixed abode.…”
mentioning
confidence: 99%